Acute Hereditary Angioedema With Airway Compromise: Avoiding Airway Intervention With C1 Inhibitor Concentrate. (11th July 2018) - Fu, WeiZhong Ernest; Tan, Sze-Chin; Ho, Eu Chin
Introduction: Hereditary angioedema (HAE) is an autosomal dominant disease caused by deficiency of the plasma protein C1 inhibitor (C1-INH). Patients classically present with recurrent localized subcutaneous or submucosal edema lasting for 2 to 5 days, severe abdominal pain, or acute airway obstruction which can be fatal. Case presentations: We highlight 2 patients with acute airway compromise secondary to HAE who were successfully treated with plasma-derived C1-INH concentrates. Conclusions: The timely administration of plasma-derived C1-INH concentrates for the acute treatment of HAE has been proven to be effective in both patients in aborting an airway complication. A high index of suspicion is required for the early diagnosis and treatment of this potentially fatal condition.